Hirarki Wilayah Kota Ternate Pasca Pengembangan Kawasan Waterfront City - Firdawaty Marasabessy (Jurnal Wilayah dan Lingkungan, 2016)
Ternate waterfront city development initiative 2006-2015 was designated for anticipating the limitation of land use due to high population increase, geographical and topographical constraints of the region, the threat of catastrophic volcanic eruption, and the national and provincial development strategies. The purpose of this study was to analyze the urban service hierarchy inside the city responding the initiative. The methodology used in this research was scalogram analysis for calculating infrastructure availability variables. The results showed that the post-implementation of waterfront city development initiative (2005-2011) the number of infrastructure availability and accessibility has improved, particularly in the coastal urban villages inside the waterfront city development area.